Impact of Personal Income on Usage of FMCG Product of Rural Consumer - Barik, Sarita; Mohanty, Lipika; Sahoo, Suchitra; Mohanty, Smita; Swain, Sukanta Chandra (Indian Journal of Information Sources and Services, 2025)
Marketing products in today's cutthroat marketplace is fraught with difficulties. There are problems that can be fixed, but there are other problems that might never be fixed. As a developing nation, India has a long way to go. As a result, the majority of the population is found in the country. Promoting business in rural areas is crucial for any nation looking to grow economically. It is extremely difficult for manufacturers to market their products in rural areas since most residents have low earnings, little education, poor brand awareness, outdated communication and transportation facilities. Making decisions on their purchases of fast-moving consumer goods is proving to be difficult for many people. It is necessary to conduct research on the fast-moving consumer goods consumption patterns of rural Odisha. The current study's goal is to investigate the connection between FMCG product use and personal income. The study, which is empirical in character, selects 300 male rural consumers. The chi-square test is employed to test the hypotheses.